EFEKTIVITAS ORGANISASI BADAN USAHA MILIK DESA DI DESA MENGGAWA KECAMATAN TAMAKO KABUPATEN KEPULAUAN SANGIHE - PALEMBANG, MEYSILIA; TAMPI, GUSTAAF; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2021)
The establishment of Village-Owned Enterprises (BUMDes) in Menggawa Village is an effort tostrengthen the economy in the village and is a means of empowering the local economy with various typesof village potentials. However, there are still problems in the management of BUMDes in Menggawavillage. So this research was conducted to determine the organizational effectiveness of Village-OwnedEnterprises (BUMDes) in Menggawa Village, Tamako District, Sangihe Islands Regency. The researchmethod used is descriptive qualitative. The focus of this study uses Steers' theory namely: goal optimization,systems perspective, stress on the aspect of human behavior. Sources of data used in this study are primaryand secondary data. Where the data collection techniques used are interviews, observation, documentation.With 4 informants. Based on the research results of the BUMDes "Batu Senggopole" in MenggawaVillage, it is still not effective where the selection of businesses that are not in accordance with the potentialof the Village results in a business that does not go well, limited human resources who manage BUMDes,and the BUMDes management is still lacking. innovative and productive in managing BUMDes. So it isnecessary to have technical guidance and tight supervision related to the management of BUMDes inMenggawa Village.Keywords: Organizational Effectiveness, Village-Owned Enterprises